Human Capital Formation: The Importance of Endogenous Longevity - Titus Galama; Hans van Kippersluis (Tinbergen Institute, 2022)
We present a theory of human capital, with its two most essential components, health capital and, what we term, skill capital, endogenously determined within the model. Using the theory, and a calibrated version of it, we uncover and highlight an important economic mechanism driving human-capital formation, socio-economic and health disparities, human-capital based economic growth, and causal relations among the stocks of wealth, skill and health, namely whether individuals can influence their own length of life (endogenous longevity). Without the ability of individuals to influence their longevity, the effects of health, skill and wealth on later-life skill and health are muted. Any additional health, skill or wealth is not used for additional investment, but essentially consumed. These findings have important implications for the modeling of, and our understanding of, human-capital formation, disparities in human capital and health, and human-capital based economic growth.
Keywords: J24; I12; J00; 330; health investment; education; human capital; health capital; dynamic optimal control; longevity